2018
DOI: 10.1542/peds.2017-1994
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing the Evaluation of Nonaccidental Trauma in a Large Pediatric Emergency Department

Abstract: With our improvement methodology, we successfully increased guideline-adherent evaluation for patients with provider concern for NAT. Education and electronic support at the point of care were key drivers for initial implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 9 publications
(10 reference statements)
0
21
0
1
Order By: Relevance
“…She/he is required to refer the case to a Pediatrician/Gynecologist/ Psychologist for a better assessment and further investigations. Physical, radiological and laboratory tests, if required would be carried out by them to confirm the initial impression [29] . If a decision is made to refer the child, it is necessary to discuss his/her concern with the parents and seek consent.…”
Section: Refer For Assessmentmentioning
confidence: 99%
“…She/he is required to refer the case to a Pediatrician/Gynecologist/ Psychologist for a better assessment and further investigations. Physical, radiological and laboratory tests, if required would be carried out by them to confirm the initial impression [29] . If a decision is made to refer the child, it is necessary to discuss his/her concern with the parents and seek consent.…”
Section: Refer For Assessmentmentioning
confidence: 99%
“…A follow-up study demonstrated that despite its accuracy (Louwers et al, 2014), the tool was only utilized half of the time, suggesting problems with adherence in a busy clinical setting. Systematic reviews also show inconsistent use and low-quality evidence for the accuracy of other screening tools (Bailhache, Leroy, Pillet, & Salmi, 2013; Riney et al, 2018). As such, developing an automated, reliable, and accurate screening system could possibly improve the detection of child maltreatment, particularly for vulnerable populations.…”
Section: Background and Significancementioning
confidence: 99%
“…Components of an abuse evaluation were not defined due to process variability and resource availability by center. Some require subspecialty abuse expert evaluation, others utilize a social worker for the abuse evaluation, and some have a protocolized approach to testing and reporting 12,13 . Best practice guidelines are available from the American Academy of Pediatrics and the American College of Surgeons to help develop local systematic programs, and every hospital must have a robust system in place 5,6 .…”
mentioning
confidence: 99%
“…Some require subspecialty abuse expert evaluation, others utilize a social worker for the abuse evaluation, and some have a protocolized approach to testing and reporting. 12,13 Best practice guidelines are available from the American Academy of Pediatrics and the American College of Surgeons to help develop local systematic programs, and every hospital must have a robust system in place. 5,6 This guideline was a collaborative effort between members of the guideline committees of the Pediatric Trauma Society (PTS), the Eastern Association for the Surgery of Trauma (EAST), and the Ray E. Helfer Society (Child Abuse Pediatrics).…”
mentioning
confidence: 99%